2014
DOI: 10.1177/0042098014558537
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant suburbanisation and the shifting geographic structure of metropolitan segregation in the United States

Abstract: This study investigates immigrant suburbanisation trends over the past decade in the metropolitan USA, focusing on how suburbanisation affects the residential segregation of foreign-born populations. Using 2000-2012 data from the decennial census and American Community Survey, it tracks the suburban settlement patterns of 17 country-of-origin groups. It uses a methodological approach that decomposes metropolitan segregation into within and between city/suburb components. The findings indicate that most immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…Ellis et al, 2012;Lee et al, 2014) or the studies compare cities and suburbs (e.g. Farrell, 2016;Pfeiffer, 2014;Sandoval, 2011). In turn, such studies are limited in their ability to locate precisely where diversity is and is not found within metropolitan areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ellis et al, 2012;Lee et al, 2014) or the studies compare cities and suburbs (e.g. Farrell, 2016;Pfeiffer, 2014;Sandoval, 2011). In turn, such studies are limited in their ability to locate precisely where diversity is and is not found within metropolitan areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have shown that suburbs become ethnically more heterogeneous over time (Timberlake, Howell, and Staight 2011;Alba et al 1999;Farrell 2014), facilitating residential integration. However, it cannot be claimed that suburbanisation marks the end of segregation -over time the suburbanisation of minority groups can also have an increasingly segregative effect within the suburb itself (Li 1998;Farrell 2014;Tammaru et al 2013). Alba et al (1999) argued that when the proportion of ethnic minorities in a suburb increases, it becomes easier for other members of that ethnic group to settle there, because the networks and social infrastructure that exist in those suburbs are now more likely to meet their expectations.…”
Section: Different Forms Of Spatial Mobility and Neighbourhood Outcomesmentioning
confidence: 99%
“…This perspective normally informs residential segregation, suburbanization, and attainment research (Farrell 2016; Iceland 2009; South et al 2008), but a scaled-up version can be applied to Latino diversity within metropolitan areas. In simplest form, the assimilation process involves two steps.…”
Section: Introductionmentioning
confidence: 99%